The Role Of Interactive Applications As Pedagogical Tool In Public Sector Universities Of Sindh, Pakistan - Hafsa,; Kalsoom,; Zain ul Abdin Rind, (Dialogue Social Science Review (DSSR), 2025)
Our students are part of a highly digitized generation with swift and effortless access to information. They rely on technology and are prone to rapid boredom. A debate persists over the necessity to reevaluate our pedagogical approaches, particularly in public universities, to engage our students effectively. This study examined students' use of interactive software in classes and their effect on university education. These applications are seen as vital instruments in alleviating student ennui and disengagement. They also allow teachers to obtain essential feedback, which educators in the poll identified as critically significant. In this context, we performed a study among students in the education department at the University of Sufism and Modern Sciences Bhitshah. We analyzed the utilization of several interactive applications (Kahoot, Padlet, Quizlet, and Microsoft). This study sought to ascertain how the utilization of numerous applications enhanced student engagement by mitigating monotony, hence leading to improved academic achievement Keywords: Pedagogical, Tools, Applications